Comparison of The Effectiveness of Business Dispute Resolution Through Mediation, Arbitration, and Litigation - Hetiyasari, Hetiyasari; Wahyuningsih, Putri; Alfarid, Alfarid; Deyau, Boy Nendra Asa (LifeSciFi, 2024)
Resolving business disputes is very important in the business world and can be done using various methods such as mediation, arbitration, and litigation, each of which has advantages and disadvantages. This research aims to compare the effectiveness of these three methods in the context of resolving business disputes in Indonesia. This research method uses a comparative design, with primary data collected through interviews and surveys, as well as secondary data from document analysis and industry reports. The research results show that mediation is the most frequently used method and produces the highest level of agreement and satisfaction between the parties. However, the level of compliance with decisions is higher in arbitration and litigation methods. Industry trends show increased use of mediation, reflecting a shift towards more efficient and cost-effective solutions. These findings imply that companies and policymakers in Indonesia should promote the use of mediation, develop mediation capacity, and ensure a supportive regulatory framework is in place. With these steps, resolving business disputes in Indonesia can become more efficient, effective, and satisfying for all parties involved.